Lifestyle Intervention on Feature of Polycystic Ovarian Syndrome in Obese Adolescent Girls (Medical Forum Monthly, 2021)
Objective: To study the lifestyle intervention on feature of polycystic ovarian syndrome in obese adolescent girls.Study Design: Prospective studyPlace and Duration of Study: This study was conducted at the Obstet and Gynecology Department, Jinnah Hospital Lahore and Sardar Begum Teaching Hospital Sialkot during Jan 2019 to April 2020.Materials and Methods: One twenty five patients of polycystic ovarian syndrome in obese adolescent girls were selected for recent study. The informed consent of every patient was taken before history examination and Ultrasonography. The permission of Ethical Committee was taken before collecting data and get publishing in Medical Journal. The data was analyzed for results by SPSS verison20.Results: One hundred twenty five girls (mean age fourteen point nine ± zero point eight yr) reduced their Body Mass Index Standard Deviation Status higher than zero point two in the lifestyle intervention, whereas fifty girls demonstrated an increase of Body Mass Index Standard Deviation Status or a reduction of Body Mass Index Standard Deviation Status less than or equal to zero point two (mean age fifteen point one ± zero point seven yr).Conclusion: The prevalence of ovarian syndrome was maximum seventy five (sixty percent) at age group twelve to fourteen and was minimum fifty (forty percent) at age group fifteen to seventeen.